Role Criminal Law Against Case Usage Identity Card (KTP) Someone Else to Make an Online Loan - Nila Indrika Anggi Finanda (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2022)
In Indonesia, 50% of online loans are made using another person's identity card (KTP), with West Java province accounting for around 50%. So this study employs normative research approaches. Role of criminal law in cases of using another person's identity (KTP) to make online loans by providing criminal sanctions in accordance with Law of Republic of Indonesia Number 27 of 2022 concerning Protection of Personal Data Article 67 paragraph (1) is punishable by a maximum imprisonment of 5 (five) years and/or a maximum fine of IDR 5,000,000,000 in conjunction with Indonesian Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions Article 48 Paragraph (1) Every person who complies with elements as intended in Article 32 paragraph (1) shall be punished with imprisonment for a maximum of 8 (eight) years and/or a fine of up to IDR 2,000,000,000. Suggestions for role of criminal law in cases of using someone else's identity (KTP) to make online loans are increasingly being implemented well and effectively, including (a) cooperation between government, legal entities, and Ministry of Information and Communications, such as ignoring suspicious links or attachments. (b) Collaboration between government, civil registration population service, and financial services authority in determining validity of a person's identity (KTP) when registering for online loans; however, this can only be done for online loans that have received operational permits from financial services authority. (c) Collaboration between government and community, such as not disclosing personal information to anybody. Second, disregard any suspicious links and only use legitimate applications. Third, update your password and make frequent backups of crucial data